Analisis Faktor Yang Mempengaruhi Tingkat Adopsi Teknologi Budidaya Bawang Merah Dari Biji - Hanif Gusrianto; Zulvera; Sri Wahyuni (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2023)
Research objectives for 1). Knowing the Adoption Rate of Shallot Technology from Seeds in Lamposi Tigo Nagori District, Payakumbuh City. 2). Analyze the factors influencing the adoption rate of Shallot Cultivation Technology from Seeds in Lamposi Tigo Nagori District, Payakumbuh City. This study was conducted with a correlative descriptive survey method, namely collecting information from a selected sample representing a population of 95 respondents using the Likert Scale questionnaire as a data collection tool. The analysis tool uses multiple regression. The results of the research in the first objective showed that the adoption rate of onion cultivation technology from seeds in Lamposi Tigo Nagari district, Payakumbuh City, was in the moderate category with an interval of 50-77 percentage of respondents 62.1%. The results of the study on the second objective showed that the constant value (α) of 69,860 explained that if the variable Internal Characteristics of Farmers for the Social Dimension (X1), the characteristics of Innovation (X3) and Extension Support (X4) are assumed to be zero, then the Adoption Rate of TSS technology (Y) is worth a constant of 69,860 units. Thus, the four research variables have a positive effect on the adoption rate of onion cultivation technology from seeds in Lamposi Tigo Nagori District, Payakumbuh City